Covid-19 e a saúde mental de adolescentes no sul de Lima, Peru - Ñañez Silva, Miriam Viviana (2022)
COVID-19 is damaging the health of the population worldwide, and generating unprecedented economic changes, whose impact is greater in countries with high rates of poverty and inequality, as is the case of Peru. This research seeks to identify the symptoms associated with mental health generated by COVID-19 in teenagers in the southern area of ​​the department of Lima, Peru. It is a basic research, quantitative approach, descriptive-level non-experimental design. The sample is probabilistic and stratified made up of 560 teenagers from secondary level (87,9%) and university education (12,1%), whose ages range from 12 to 21 years, being 311 women and 249, men. The results indicate that 60.1% experience sadness; 53.1%, fear; 52.6%, excessive concern; 51.3%, difficulty staying still; 46.6%, alteration in diet; 43.2%, feeling of emptiness and 40.3%, difficulty in making decisions. Likewise, 45.6% feel the appearance or increase of anxious symptoms and 36.8%, depressive symptoms. We can conclude that the COVID-19 pandemic and associated factors such as social isolation generate the appearance of symptoms that affect the mental health of adolescents, linked to anxiety and depressive disorders, with a greater preponderance in women.